Pembangunan Ekonomi di Masa Pemerintahan Dinasti Fatimiyyah - Anshary, Ahmad Hafiz (Islamic Economics and Business Faculty of UIN Antasari, 2016)
Abstract: The Fatimid is one of the big dynasty that has successful in economic development. In its heyday, this dynasty was very rich and all people life in prosperous. The state's revenues derived from two sources: the community and government business. Revenues from the community, i.e: tax, al-iqtha’, al-jizya, zakat, excise, al-ahbas, al-mawarits al-hasyriyyah, al-amwal al-mashadirah, and the government's business include: hotel’s and shop’s rentals income, trades, industry, and other economy sectors owned by the government. This dynasty build many of economic sectors include: agriculture and plantations such as wheat, sugarcane, and fruits with a good irrigation system; crafts, such as the manufacture of ships, weapons, woven, and household appliances; and trade, both at domestic and abroad. The economic development success is one of the factor this dynasty was able to maintain its power more than 250 years (297-567 H / 909-1171 AD).Abstrak: Fatimiyah adalah salah satu dinasti besar yang sukses membangun perekonomiannya. Pada masa jayanya, dinasti ini sangat kaya dan rakyat hidup sejahtera. Pendapatan negara diperoleh dari dua sumber: Masyarakat dan usaha pemerintah. Pendapatan dari masyarakat antara lain: al-kharaj, al-iqtha’, al-jizyah, zakat, al-mukus, al-ahbas, al-mawarits al-hasyriyyah, al-amwal al-mashadirah, dan usaha pemerintah di antaranya: hasil persewaan hotel-hotel dan toko-toko, perdagangan, industri, dan sektor-sektor perekonomian milik pemerintah. Sektor-sektor ekonomi yang dibangun meliputi: Pertanian dan perkebunan seperti gandum, tebu, dan buah-buahan dengan sistem irigasi yang baik; kerajinan, seperti pembuatan kapal laut, senjata, tenunan, dan alat-alat rumah tangga; dan sektor perdagangan, baik perdagangan di dalam maupun di luar negeri. Keberhasilan di bidang ekonomi merupakan salah satu faktor penyebab dinasti ini mampu berkuasa lebih dari 250 tahun (297-567 H/909-1171 M).